Pembangunan kesehatan masyarakat melalui pos pelayanan terpadu = The Development of Public Health Through The Integrated Health Service Station - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
The aim of the research is to examine the success of integrated service station (POSYANDU) as broad health service delivery system and the factors which affect it. The research is based on synthesis of a 'self help' approach, a "technical intends to prove that the success of the program development is influenced by the integration of the following of three factors: program, beneficiaries, and assisting organization. The study is conducted in Mlonggo district, Jepara regency, with a sample of 10 POSYANDU taken purposively, within with a sample of 20 housewives having children under five years of age was taken at random from its POSYANDU. In addition, 39 active cadres from all the chosen POSYANDU are also included in the sample. Data is collected through questionnaires, administrative files, and interview guide, while its analysis is made through the use of product moment and regresion statistics. The result shows the following conclusions or findings. First, the hypothesis mentions that the social and economic condition of the people has apositive relationship with the achievement of POSYANDU (defined as partitionship of the people in the program and the scope of POSYANDU program) is not proven, especially with regard to the preventive service element of the program (weighing the children uner five years of age, imunization, and provision better nutrition). Its finding shows that only people from low social and economic strata who took advantage of the program service, the majority of people in the district do not utilaze the program service. Second, the hypothesis states that the compatibility of the program output and beneficiary needs is positively correlated with the achievement of POSYANDU is found to be irnpericaly proven_ Third, the hypothesis that the compatibility ofthe mechanisms for beneficiary demand expression and the decision processes of the assisting organization is positively related with the achievement of POSYANDU is also proven. Fourth,the hypothesis that the compatibility of the program task requirements and the distinctive competence of the assisting organization (with regard to man power, fund and mens) is be positively correlated with the achievement of POSYANDU is also found empiricaly proven.